Live Musik, Syariat Islam dan Asas Freies Ermessen: Menyikapi Surat Edaran Bupati Bireuen - Syah Iskandar; Edi Saputra (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2023)
The prohibition order on live music in the the Regent of Bireuen's Letter of Interdiction No. 451/199/2023 was pro-contracted in the community; some people supported the Islamic Shariah, and some others rejected it on the grounds of the lack of consistency of the instructions in the edaran. The Edaraan has been identified as allowing live music to beined with conditions that are difficult to realize. This has caused confusion in the public's understanding of the Regent of Bireuen's orders. The objective of the research is to analyze the existence of the implementation of the Regent of Bireuen's Letter of Interdiction with the basic approach of Freies Ermessen and its implications for the observance of Bireuen society. This research uses a yuridis-empirical method; data is collected with interview, and analyzed with analytical-descriptive techniques. The results of the research show that the existence of Regent of Bireuen's Letter of Interdiction of Live Music undermines the discretion of the government and, as contextually indicated, violates the basic principles of Freies Ermessen, thus having no legality in the hierarchy of legislation. However, if the government considers that live music needs to be banned in order to support the enforcement of Shariah Law, then it is regulated by a law that includes the study of academic scripts. In this way, he gives birth to a good law according to the will of the people.